2001
DOI: 10.1300/j069v21n01_07
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Deficits Among Methamphetamine Users with Attention Deficit Hyperactivity Disorder Symptomatology

Abstract: Understanding the association between attention deficit hyperactivity disorder (ADHD) and substance abuse, specifically methamphetamine (MA) abuse, is challenging, partly because little is known about the specific constellation of cognitive impairments produced by MA. The present investigation serves to address this relationship by comparing the cognitive performance of MA abusers with ADHD symptomatology (n = 28) and MA abusers without ADHD symptomatology (n = 41) on tests of attention, memory and general int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…However, evidence for enduring executive dysfunction in abstinent drug addicts has been less well substantiated despite research indicating a reduced metabolism in the orbital PFC of chronic cocaine abusers 3-4 months after drug discontinuation (Volkow et al 1993). Even more problematic is the frequently encountered coexistent psychopathology that may precede drug addiction (Khantzian 1985;Levin and Kleber 1995;Sim et al 2002;Dawe and Loxton 2004). Using a task in which proficient performance depends on the integrity of the PFC and striatum (Robbins 2002), the present study addresses these issues by allowing controlled drug access to subjects premorbidly assessed for cognitive capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence for enduring executive dysfunction in abstinent drug addicts has been less well substantiated despite research indicating a reduced metabolism in the orbital PFC of chronic cocaine abusers 3-4 months after drug discontinuation (Volkow et al 1993). Even more problematic is the frequently encountered coexistent psychopathology that may precede drug addiction (Khantzian 1985;Levin and Kleber 1995;Sim et al 2002;Dawe and Loxton 2004). Using a task in which proficient performance depends on the integrity of the PFC and striatum (Robbins 2002), the present study addresses these issues by allowing controlled drug access to subjects premorbidly assessed for cognitive capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult, however, to be sure that long-term effects are necessarily limited to abuse of a particular drug in polydrug abusers, or to take into account confounding effects of comorbidity for other forms of psychiatric disorder (eg, see Sim et al, 2002). In this study, we have shown clear, persistent effects of MDMA withdrawal to impair attentional performance under challenge, and actually to reduce the vigor of behavioral output in terms of long-term reductions in impulsive responding (see also Montgomery et al, 2006), lengthening of magazine latency (to collect earned food pellets), and increased omissions.…”
Section: Implications For Cognitive Sequelae Of Human Drug Abusementioning
confidence: 99%
“…Studies in human drug abusers support the existence of specific psychological deficits during acute drug withdrawal (Simon et al, 2000;Sim et al, 2002;Kalechstein et al, 2003), but there is a lack of reliable data on the long-term neurocognitive profile of abstinent stimulant abusers. Even more difficult is that drug abuse may coexist with other neuropathologies that may, in some circumstances, predate drug-taking behavior (Khantzian, 1985;Levin and Kleber, 1995;Sim et al, 2002). For these reasons, studies using animal models are especially important to establish the long-term effects on cognition of amphetamine and other drugs of abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Abusers of the drug have been found to be cognitively impaired the areas of attention, psychomotor speed, learning, memory, executive functions and decision-making. Some may even suffer loss of spontaneous movement, similar to Parkinson's disease [27][28][29] . Opiates have been found to induce impairments in the areas of attention, information processing, problem solving, coordination, working memory and psychomotor speed and performance [30][31][32][33][34] .…”
Section: Introductionmentioning
confidence: 99%